Design and development of doctor’s dictation kit using raspberry PI - Haque, Kazi Injamamul; Saha, Ullash; Biswas, Sudipto; Billah, Md. Muhtasim; Momin, Abu Saleh Al (BRAC University, 2017)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2016.